2022
DOI: 10.54941/ahfe1001481
|View full text |Cite
|
Sign up to set email alerts
|

Human Gait Recognition Using Bag of Words Feature-Representation Method

Abstract: In this paper, we propose a novel gait recognition method based on a bag-of-words feature representation method. The algorithm is trained, tested and evaluated on a unique human gait data consisting of 93 individuals who walked with comfortable pace between two end-points during two different sessions. To evaluate the effectiveness of the proposed model, the results are compared with the outputs of the classification using extracted features. As it is presented, the proposed method results in signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Hand-selected features can be applied to the time domain, frequency domain, or time-frequency domain to select signal characteristics involving signal energy or complexity to increase the class separability and robustness of the recorded signal 25 . However, these extracted features are susceptible to including unnecessary or redundant features within and/or between the domains 26 . There is a general redundancy (overlap) of features between time and frequency domains, and it was shown that the time domain features are superior to frequency domain features due to their low complexity 27 .…”
Section: Signal Qualitymentioning
confidence: 99%
“…Hand-selected features can be applied to the time domain, frequency domain, or time-frequency domain to select signal characteristics involving signal energy or complexity to increase the class separability and robustness of the recorded signal 25 . However, these extracted features are susceptible to including unnecessary or redundant features within and/or between the domains 26 . There is a general redundancy (overlap) of features between time and frequency domains, and it was shown that the time domain features are superior to frequency domain features due to their low complexity 27 .…”
Section: Signal Qualitymentioning
confidence: 99%
“…In other words, the average precision is the area under the precisionrecall curve for each categories of objects. The mean average precision is computed by taking the mean of the average precision for all category of objects [13], [33]. Figure 3 shows the Faster-RCNN results of detection when tested on the PASCAL VOC2007 test data in various levels of resolution (R 1 , ..., R 20 ) as explained in the previous section.…”
Section: A Performance Evaluation Of the Faster-rcnn On Different Res...mentioning
confidence: 99%
“…Pada penelitian ini peneliti menggunakan dua model ekstraksi fitur antara lain adalah Bag of Words Model dan Term Frequency-Inverse Dokumen Frequecy (TF-IDF). Bag of Words merupakan suatu cara sederhana dalam menghitung frekuensi kemunculan kata dalam dokumen [10]. Adapun TF-IDF merupakan sebuah proses mengubah token (term) menjadi nilai numerik yang dapat dibaca oleh komputer, tujuannya agar sistem dapat mengevaluasi seberapa pentingnya sebuah term pada suatu dokumen [11].…”
Section: Ekstraksi Fiturunclassified